The Effect of Auditor Competence, Independence, and Moral Reasoning on Audit Quality (Empirical Study at Financial and Development Supervisory Agency of Maluku Province) - Tirza Oktovianti Lenggono (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2022)
This research intends to examine the effect of auditor competence, independence, and moral reasoning on audit quality at Financial and Development Supervisory Agency of Maluku Province Representative. The sample in this research comprises all auditors who work at Maluku Province Financial and Development Supervisory Agency, with a total of 59 auditors utilizing a questionnaire survey approach and measured using a Likert scale. There are 59 distributed questionnaires, and 45 returnedquestionnaires. Multiple linear regression analysis is used to analyze the data, which is carried out using the SPSS version 21 program. The findings of this study indicate that auditor expertise has a significant effect on audit quality in part. Independent auditors have a significant impact on audit quality. Additionally, moral reasoning has a significant impact on audit quality.